2022
DOI: 10.1039/d1qi01672e
|View full text |Cite
|
Sign up to set email alerts
|

Highly dispersed Ru nanoclusters anchored on B,N co-doped carbon nanotubes for water splitting

Abstract: We developed an N, B co-doped carbon nanotubes as a substrate material to load 2-3 nm uniform Ru clusters. We rationally realized controllable N and B doping into carbon nanotubes....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In the B 1s fine spectrum of Pt/B 4 C, shifts of 0.16, 0.41, and 0.6 eV to the right for the B–O bond, B–C bond, and B–B bond peaks were observed after Pt deposition, respectively. 20,44 Comparison with the B 1s binding energy states of B 4 C and Pt/B 4 C reveals that the B 1s was in an electron-rich state after Pt deposition. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the B 1s fine spectrum of Pt/B 4 C, shifts of 0.16, 0.41, and 0.6 eV to the right for the B–O bond, B–C bond, and B–B bond peaks were observed after Pt deposition, respectively. 20,44 Comparison with the B 1s binding energy states of B 4 C and Pt/B 4 C reveals that the B 1s was in an electron-rich state after Pt deposition. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Zou et al reported the synthesis of Ru nanoclusters with particle size of 2–3 nm supported on boron and nitrogen co-doped carbon nanotubes (Ru@B,N-CNTs) by a mild solution blending and post calcination method. 137 The as-obtained Ru@B,N-CNTs diplays a low overpotential of 315 mV, outperforming the activities of B,N-CNTs (467 mV), Ru@B-CNTs (378 mV), Ru@N-CNT (409 mV) and commercial RuO 2 (390 mV). Moreover, Ru@B,N-CNTs also exhibits a high durability by retaining its activity even after 36 h chronopotentiometry test at 10 mA cm −2 in base media, which is ascribed to stability enhancement caused by the carbon support through synergistic modulation of the electronic structure via the N and B doping.…”
Section: Ru Metalsmentioning
confidence: 93%
“…For example, the B, N co-doped carbon nanotubes (B, N-CNTs) are used as promising matrices for Ru nanoclusters. 231 Ru@B, N-CNTs display excellent bifunctional performance for HER/OER with low overpotential and outstanding stability under alkaline conditions. Moreover, the Ru nanoparticles are embedded into N-modified carbon spheres (Ru/NPCS) by Xing's group.…”
Section: Nanostructure Engineering Of Ru-modified Electrocatalystsmentioning
confidence: 99%